The Process of Globalization, its Interface With the Culture and Communication (Revista Brasileira Multidisciplinar, 2010)
This work discusses how and in which points and ways the globalization process influences our daily life, pointing out the final positive and negative sides resulting from this intervention. Besides, it also focuses on the mass culture, emphasizing its effects and importance to the economic and social aspects as well as to the political and ideological ones in our current context.
Keywords: Cultural industry; Media culture; Globalization